Factors that influence female consumer purchase intention toward fashion apparel - Siti Hamizah Suboh, 1992-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2015